Anisotropic light diffusion film, display film using the same, and display
Patent Information
- Application Number
- CN202580025202.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-30
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]但是,近年来,对低温环境的要求变得更严格,在更低温(-15℃)下,有可能无法得到对弯曲的充分效果
[0031]根据本发明,能够提供各向异性光扩散膜、使用该各向异性光扩散膜的显示器用膜以及使用该显示器用膜的显示器,该各向异性光扩散膜在需要弯曲的显示器或弯曲的窗等中,即使在-15℃~60℃下使用的情况下,也不会发生裂纹、褶皱等异常。
Smart Images

Figure CN123022972A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to anisotropic light diffusion films, display films using the anisotropic light diffusion films, and displays.
[0002] This application claims priority based on Japan Patent Application No. 2024-73990 filed on April 30, 2024, the contents of which are incorporated herein by reference. Background Technology
[0003] Anisotropic light diffusion films are effective light diffusion films in the display field for improving viewing angle, increasing brightness, and improving image quality. In addition, as window films, they are used as effective films for transparent screens or for maintaining privacy.
[0004] However, in the pursuit of increased brightness in displays, the strain on the eyes has increased, potentially leading to decreased vision. Therefore, attempts have been made to reduce eye strain by using an anti-glare (AG) film on the display surface to suppress strong brightness from the front, thereby reducing the reflectivity of external light. However, in the case of high-resolution displays, pixels are mixed according to the size of the AG film's unevenness, resulting not only in glare such as flicker caused by interference, but also in a reduction in contrast. To address this, Patent Document 1 discloses an anti-glare film that, by combining an anti-glare layer and an anisotropic light diffusion layer, can eliminate flicker while suppressing a reduction in contrast.
[0005] On the other hand, recently there has been an expansion of anisotropic light diffusion films into applications such as curved displays or windows. The required performance of such anisotropic light diffusion films is that they should not crack, wrinkle, or exhibit other abnormalities even when used in a curved state in environments ranging from low to high temperatures.
[0006] In patent document 2, a light diffusion control film that specifies the relationship between energy storage modulus and loss modulus is proposed to improve the flexibility at 5°C.
[0007] However, in recent years, the requirements for low-temperature environments have become more stringent. At even lower temperatures (-15°C), it may not be possible to achieve sufficient bending performance. Furthermore, at high temperatures of 60°C, it may also be impossible to achieve sufficient bending performance.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: International Publication No. 2018 / 180541
[0011] Patent Document 2: Japanese Patent Application Publication No. 2019-144418 Summary of the Invention
[0012] The technical problem that the invention aims to solve
[0013] The present invention provides an anisotropic light diffusion film, a display film using the anisotropic light diffusion film, and a display. The anisotropic light diffusion film will not crack or wrinkle in displays or windows that need to be bent, even when used at temperatures ranging from -15°C to 60°C.
[0014] Technical solutions for solving technical problems
[0015] The present invention includes the following methods.
[0016] [1] An anisotropic light diffusion film having an anisotropic light diffusion layer, wherein the anisotropic light diffusion layer is formed by photopolymerization of a composition comprising a photopolymerizable compound, a photopolymerization initiator and at least one plasticizer selected from ester, epoxy and liquid rubber systems, wherein the anisotropic light diffusion film is characterized in that the anisotropic light diffusion layer has a matrix region and a columnar region, wherein the columnar region is composed of a plurality of columnar structures with a refractive index different from that of the matrix region.
[0017] [2] According to the anisotropic light diffusion film described in [1], the anisotropic light diffusion layer has a storage modulus of 1.0 × 10⁻¹⁰ at -15°C. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7 Pa ~ 2.0 × 10 9 Pa, the energy storage modulus of the anisotropic light diffusion layer at 25°C is 1.0 × 10⁻⁶. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7 Pa ~ 2.0 × 10 9 Pa, the energy storage modulus of the anisotropic light diffusion layer at 60°C is 1.0 × 10⁻⁶. 6 Pa ~ 2.0 × 10 8 Pa and loss modulus are 1.0 × 10 6 Pa ~ 2.0 × 10 8 Pa.
[0018] [3] The anisotropic light diffusion film according to [1] or [2] is characterized in that the loss tangent of the anisotropic light diffusion layer at -15℃ to 60℃ is 0.07 to 0.8.
[0019] [4] The anisotropic light diffusion film according to any one of [1] to [3] is characterized in that the peak temperature of the lowest temperature side of the loss tangent of the anisotropic light diffusion layer is below 0°C.
[0020] [5] The anisotropic light diffusion film according to any one of [1] to [4] is characterized in that the plasticizer is used in proportions of 30% or less of the total composition.
[0021] [6] The anisotropic light diffusion film according to any one of [1] to [5] is characterized in that the linear transmittance at an incident light angle of 0° is 1% or more and less than 20%, the linear transmittance at an incident light angle of 15° is 1% or more and less than 20%, and the linear transmittance at an incident light angle of 45° is 30% or more and less than 80%.
[0022] [7] The anisotropic light diffusion film according to any one of [1] to [6] is characterized in that the aspect ratio of the cross section of the columnar structure perpendicular to the column axis is less than 2.
[0023] [8] The anisotropic light diffusion film according to any one of [1] to [6] is characterized in that the aspect ratio of the cross section of the columnar structure perpendicular to the column axis is 2 to 40.
[0024] [9] The anisotropic light diffusion film according to any one of [1] to [8] is characterized in that the thickness of the anisotropic light diffusion layer is 10 μm to 60 μm.
[0025]
[10] The anisotropic light diffusion film according to any one of [1] to [9] is characterized in that the plasticizer is a photocurable compound.
[0026]
[11] The anisotropic light diffusion film according to any one of [1] to [9] is characterized in that the plasticizer is a thermosetting compound, the composition further comprises a curing agent, and the anisotropic light diffusion layer is composed of light and thermally polymerized light added in the photopolymerization.
[0027]
[12] A display film, characterized in that the display film has an anisotropic light diffusion film as described in any one of [1] to
[11] and an anti-glare layer on the visual confirmation side of the anisotropic light diffusion layer.
[0028]
[13] The display film according to
[12] is characterized in that the arithmetic mean roughness of the anti-glare layer is 0.05 μm to 1.00 μm.
[0029]
[14] A display, characterized in that the display has the display film described in
[12] or
[13] in such a way that the anti-glare layer is the most visually verifiable side.
[0030] Invention Effects
[0031] According to the present invention, an anisotropic light diffusion film, a display film using the anisotropic light diffusion film, and a display using the display film can be provided. The anisotropic light diffusion film will not crack, wrinkle, or other abnormalities even when used in displays or windows that require bending, even at temperatures ranging from -15°C to 60°C. Attached Figure Description
[0032] Figure 1 This is a schematic cross-sectional view illustrating one embodiment of the anisotropic light diffusion film of the present invention.
[0033] Figure 2 This is a schematic cross-sectional view illustrating one embodiment of the display film of the present invention.
[0034] Figure 3 This is a schematic cross-sectional view illustrating other examples of the display film of the present invention.
[0035] Figure 4 This is a schematic cross-sectional view illustrating other examples of the display film of the present invention.
[0036] Figure 5 This is a schematic diagram illustrating a first example of a method for manufacturing an anisotropic light diffusion film according to the present invention, including any of steps 1-3.
[0037] Figure 6 This is a schematic diagram illustrating a second example of a method for manufacturing an anisotropic light diffusion film according to the present invention, including any of steps 1-3.
[0038] Figure 7 This is an explanatory diagram illustrating the evaluation method for the linear transmittance of an anisotropic light diffusion layer. Detailed Implementation
[0039] The meanings of the main terms in this specification and claims are as follows.
[0040] An "anisotropic light diffusion layer" refers to a light diffusion layer that exhibits incident light angle dependence and whose diffusion properties vary with the incident light angle. In other words, it is a light diffusion layer whose linear transmittance varies with the incident light angle.
[0041] An anisotropic light diffusion film refers to a film mainly composed of an anisotropic light diffusion layer. In addition to the anisotropic light diffusion layer, it may also have other layers (e.g., adhesive layer, functional layer, transparent film layer, etc.). Alternatively, it can be a single anisotropic light diffusion layer.
[0042] "Linear transmittance" refers to the ratio of the amount of light transmitted in a straight line (linear transmittance) to the amount of incident light when light is incident on an anisotropic light diffusion film (anisotropic light diffusion layer) at a certain incident angle, expressed by the following formula. The straight line direction indicates the direction of travel of the incident light. The linear transmittance can be measured by the method described in paragraph 0157 of Japanese Patent Application Publication No. 2015-191178 or in the embodiments of this application specification.
[0043] Linear transmittance (%) = (Linear transmitted light quantity / Incident light quantity) × 100
[0044] "Maximum linear transmittance" refers to the linear transmittance of light incident at the angle of incidence with the maximum linear transmittance.
[0045] "Minimum linear transmittance" refers to the linear transmittance of light incident at the angle of incidence with the minimum linear transmittance.
[0046] The "scattering center axis" refers to the direction in which the light diffraction is consistent with the incident light angle of light that is approximately symmetrical with respect to the incident light angle when the incident light angle to the anisotropic light diffusion layer is changed.
[0047] Here, "approximately symmetrical" is used because, when the scattering center axis is tilted relative to the normal direction of the anisotropic light diffusion layer, the optical properties (hereinafter referred to as the "optical profile") are not strictly symmetrical. The scattering center axis can be identified by the incident light angle, which is approximately symmetrical, within this optical profile.
[0048] "Optical profile" refers to the graph of linear transmittance values relative to an anisotropic light diffusion layer as the incident light angle changes. The optical profile does not directly represent light diffusion, but if it is interpreted as an increase in diffuse transmittance due to a decrease in linear transmittance, it can be said to roughly represent the incident angle dependence of light diffusion.
[0049] Furthermore, the incident light angle at approximately the center of the optical profile, which is sandwiched by the minimum value, is the scattering center axis angle.
[0050] In this invention, "scattering" and "diffusion" have the same meaning.
[0051] Both "photopolymerization" and "photocuring" refer to the polymerization reaction of photopolymerizable compounds through light.
[0052] (Meth)acrylates refer to either acrylates or methacrylates.
[0053] [Anisotropic light diffusion film and display film using the anisotropic light diffusion film]
[0054] Referring to the accompanying drawings, embodiments of the anisotropic light diffusion film of the present invention and a display film using the anisotropic light diffusion film are illustrated.
[0055] Figure 1 This is a schematic cross-sectional view showing an example of an anisotropic light diffusion film 3 according to one embodiment of the present invention.
[0056] Figure 2 This is a schematic cross-sectional view showing an example of a display film 10 according to an embodiment of the present invention.
[0057] The anisotropic light diffusion film 3 of this embodiment can be used not only for the display film 10, but also for curved windows, etc.
[0058] This invention provides an anisotropic light diffusion film 3, which, even when used in curved displays or curved windows at temperatures ranging from -15°C to 60°C, will not exhibit abnormalities such as cracks or wrinkles. Therefore, in the anisotropic light diffusion film 3 of this invention, the anisotropic light diffusion layer 30 contains at least one plasticizer selected from ester-based, epoxy-based, and liquid rubber-based plasticizers.
[0059] The display film 10 of this embodiment includes an anti-glare layer 1 and an anisotropic light diffusion film 3. The anti-glare layer 1 is disposed on the visually verifiable side of the anisotropic light diffusion layer in the anisotropic light diffusion film 3. Furthermore, although optional, a light-transmitting substrate 5 and a transparent adhesive layer 7 are also provided between the anti-glare layer 1 and the anisotropic light diffusion film 3.
[0060] The first surface 1a of the anti-glare layer 1 is an uneven surface. On the second surface 1b opposite to the first surface 1a of the anti-glare layer 1, a light-transmitting substrate 5, a transparent adhesive layer 7, and an anisotropic light-diffusing film 3 are sequentially laminated. Typically, the display film 10 has an anti-glare layer laminate 9, in which the anti-glare layer 1 is formed on one surface of the light-transmitting substrate 5, and an anisotropic light-diffusing film 3, laminated via the transparent adhesive layer 7.
[0061] However, the structure of the display film of the present invention is not limited to this structure.
[0062] (Anisotropic light diffusion layer)
[0063] Figure 1 This is a schematic cross-sectional view showing an example of an anisotropic light diffusion film 3 according to one embodiment of the present invention, which is composed of a single layer of anisotropic light diffusion layer 30. The anisotropic light diffusion film 3 may be composed of only the anisotropic light diffusion layer 30, or it may have layers other than the anisotropic light diffusion layer 30 (e.g., adhesive layer, functional layer, transparent film layer, etc.).
[0064] The anisotropic light diffusion layer 30 has a matrix region 31 and a columnar region 32, the columnar region 32 being composed of a plurality of columnar structures 33 with a refractive index different from that of the matrix region 31. The plurality of columnar structures 33 extend from one surface side to the other surface side of the anisotropic light diffusion layer 30, respectively.
[0065] One end of the columnar structure 33 reaches one surface of the anisotropic light diffusion layer 30. The other end of the columnar structure 33 may or may not reach the other surface of the anisotropic light diffusion layer 30. Both ends of the columnar structure 33 may also not reach the surface of the anisotropic light diffusion layer 30.
[0066] In this example, the columnar structure 33 extends in the same direction as the thickness direction (normal direction) of the anisotropic light diffusion layer 30. However, the anisotropic light diffusion layer 30 is not limited to this and may also be tilted relative to the thickness direction of the anisotropic light diffusion layer 30.
[0067] The refractive index of the matrix region 31 only needs to be different from that of the columnar structure 33, but the degree of difference is not particularly limited and is relative. When the refractive index of the matrix region 31 is lower than that of the columnar structure 33, the matrix region 31 becomes a low-refractive-index region. Conversely, when the refractive index of the matrix region 31 is higher than that of the columnar structure 33, the matrix region 31 becomes a high-refractive-index region. Here, it is preferable that the refractive index at the interface between the matrix region 31 and the columnar structure 33 gradually increases. By making the refractive index gradually increase, the change in light diffraction when the incident light angle changes is extremely rapid, making it difficult for flickering to occur. By forming the matrix region 31 and the columnar structure 33 through phase separation accompanying light irradiation, the refractive index at the interface between the matrix region 31 and the columnar structure 33 can be made to gradually increase.
[0068] The average height H of the columnar structures 33 in the thickness direction of the anisotropic light diffusion layer 30 is 80% or more, preferably 90% or more, and more preferably 95% or more of the thickness T of the anisotropic light diffusion layer 30. As long as the ratio of the average height H to the thickness T is above the lower limit value, the front contrast is unlikely to be reduced.
[0069] If the ratio of average height H to thickness T is above the lower limit, the interface between the matrix region 31 and the columnar structure 33 will not be interrupted and will exist continuously over a certain range in the thickness direction of the anisotropic light diffusion layer 30. Therefore, light incident from a direction inclined relative to the scattering center axis of the anisotropic light diffusion layer 30 is difficult to scatter.
[0070] The upper limit of the average height H relative to the thickness T is not particularly limited, but is preferably 100%.
[0071] The average height H of the columnar structures 33 can be determined by using an optical microscope to measure the height of 20 columnar structures 33 and using their average value. The height of the columnar structure 33 refers to the height from the bottom to the top of the columnar structure 33 when the anisotropic light diffusion layer 30 is placed horizontally with one surface as the bottom and the other surface as the top.
[0072] There are no particular restrictions on the cross-sectional shape of the columnar structure 33 perpendicular to the extension direction. For example, it can be a circular shape, an elliptical shape, a polygonal shape, an irregular shape, or a combination of these shapes.
[0073] For the cross-sectional shape of the columnar structure 33 perpendicular to the extension direction (column axis direction), the length is expressed using the minor axis, major axis, or diameter. In the case of a circular cross-section, instead of referring to them as minor and major axes, the diameter of the circle is called the diameter. In the case of an elliptical cross-section, the length of the minor axis is called the minor axis, and the length of the major axis is called the major axis. In the case of a polygonal or irregular cross-section, within the outline of these shapes, the length between the two shortest points is called the minor axis, and the length between the two longest points is called the major axis.
[0074] When the average minor diameter or diameter of the 20 columnar structures 33 is set as SA, and the average major diameter or diameter of the 20 columnar structures 33 is set as LA, in the case that the columnar structures are rod-shaped columnar structures, the aspect ratio (LA / SA), expressed as the ratio of LA to SA, can be less than 2, more preferably less than 1.5, and even more preferably less than 1.2. The lower limit of the aspect ratio is 1. That is, LA and SA can also be the same value. If the aspect ratio is less than 2, the effect of suppressing the reduction of frontal contrast is better.
[0075] When the columnar structure is a plate-shaped louver structure, the aspect ratio can also be 2 to 40.
[0076] The length of LA is at least the length of SA, preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 1.5 μm or more. By making LA a value greater than or equal to the stated value, there is a tendency to expand the diffusion range.
[0077] The LA is preferably 8.0 μm or less, more preferably 3.0 μm or less, and even more preferably 2.5 μm or less. By keeping the LA to this value or less, there is a tendency for the change in diffraction to become gradual when the incident light angle is changed, and flickering and light interference (rainbow) can be prevented.
[0078] These lower and upper limits of diffusion range (LA) can be appropriately combined. For example, by making the LA of the columnar structure 33 0.5 μm to 8.0 μm, the diffusion range can be expanded, and the change in diffraction when the incident light angle is changed becomes more gradual, which tends to further suppress the occurrence of flicker and light interference.
[0079] The length of SA is at least less than or equal to the length of LA, preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 1.5 μm or more. When SA is at or above the above values, it tends to have better light diffusion / focusing properties.
[0080] SA is preferably 5.0 μm or less, more preferably 3.0 μm or less, and even more preferably 2.5 μm or less. When the short diameter SA is below the above values, there is a tendency for the diffusion range to be further expanded.
[0081] The lower and upper limits of these SA values can be appropriately combined. For example, by making the SA of the columnar structure 33 0.5 μm to 5.0 μm, it tends to have a wider diffusion range and better light diffusivity / focusing properties.
[0082] The cross-sectional shape of the columnar structure 33, which is perpendicular to the extension direction, can be confirmed by observing the surface of the anisotropic light diffusion layer 30 using an optical microscope.
[0083] LA and SA respectively use optical microscopes to observe the surface of the anisotropic light diffusion layer 30, and measure the major axis, minor axis or diameter of the cross-sectional shape of 20 randomly selected columnar structures 33, and calculate it from their respective average values.
[0084] The aspect ratio is the value obtained by dividing the calculated LA by SA.
[0085] The anisotropic light diffusion layer 30 has a scattering central axis. When there are multiple columnar regions 32 composed of multiple columnar structures 33 in the planar direction of the anisotropic light diffusion layer 30 (for example, when adjacent columnar regions 32 are divided only by matrix regions 31 excluding columnar structures 33), the scattering central axis can also be defined for each columnar region 32. When multiple columnar structures 33 are distributed throughout the anisotropic light diffusion layer 30, a scattering central axis can also be defined over the entire anisotropic light diffusion layer 30.
[0086] In the columnar region 32 of the anisotropic light diffusion layer 30, a plurality of columnar structures 33 are formed such that the extension direction of the columnar structure 33 is parallel to the scattering central axis of the columnar region 32.
[0087] The extension direction of the columnar structure 33 is parallel to the scattering central axis of the columnar region 32 as long as the refractive index law (Snell's law) is satisfied; strict parallelism is not required. Snell's law states that when light is incident from a medium with refractive index n1 to the interface of a medium with refractive index n2, the relationship n1sinθ1 = n2sinθ2 holds between the incident angle θ1 and the refraction angle θ2. For example, if n1 = 1 (air) and n2 = 1.51 (anisotropic light diffusion layer), then with an incident angle (scattering central axis angle) of 30°, the extension direction (refraction angle) of the columnar structure 33 is approximately 19°. However, even if the incident angle and refraction angle are different, as long as Snell's law is satisfied, it is still included in the concept of parallelism in this approach.
[0088] Light incident on the anisotropic light diffusion layer 30 at a predetermined incident angle diffuses preferentially when the incident angle is approximately parallel to the extension direction (orientation direction) of the columnar structure 33, and transmits preferentially when the incident angle is not approximately parallel to the extension direction. Therefore, if the angle of light incident on the anisotropic light diffusion layer 30 changes, the linear transmittance also changes. Specifically, in the anisotropic light diffusion layer 30, within the incident angle range close to the extension direction of the columnar structure 33 (diffusion region), the incident light diffuses strongly, but in other incident angle ranges (non-diffusion region), diffusion weakens, and the linear transmittance increases.
[0089] The scattering center axis angle of the anisotropic light diffusion layer 30 is preferably -45° to +45°, more preferably -40° to +40°, and even more preferably -35° to +35°. The scattering center axis angle is the polar angle θ formed by the normal of the anisotropic light diffusion layer 30 and the scattering center axis. If the scattering center axis angle is within the range described above, the contrast is better.
[0090] The sign of the scattering center axis angle is relative to the planes on both sides of the predetermined axis of symmetry in the surface direction of the anisotropic light diffusion layer 30 and the normal direction of the anisotropic light diffusion layer 30. The case where the scattering center axis is tilted to one side is defined as positive (+), and the case where it is tilted to the other side is defined as negative (-).
[0091] Here, the predetermined axis of symmetry refers, for example, to the MD (Machine Direction) passing through the centroid of the anisotropic light diffusion layer 30. In this invention, MD is the coating direction during the fabrication of the anisotropic light diffusion layer.
[0092] The scattering center axis angle, i.e., the polar angle θ, is measured using a variable angle photometer.
[0093] The scattering center axis angle can be adjusted to the desired angle when manufacturing the anisotropic light diffusion layer 30 by changing the direction of the light irradiating the sheet-like photocurable resin composition layer (anisotropic light diffusion film composition layer).
[0094] The linear transmittance of the anisotropic light diffusion film 3 at an incident light angle of 0° is preferably 1% or more and less than 20%, the linear transmittance at an incident light angle of 15° is preferably 1% or more and less than 20%, and furthermore, the linear transmittance at an incident light angle of 45° is more preferably 30% or more and less than 80%.
[0095] By setting the linear transmittance of the anisotropic light diffusion film 3 to the range described above (preferably satisfying the numerical ranges of linear transmittance at incident light angles of 0° and 15°, and more preferably satisfying the numerical ranges of linear transmittance at incident light angles of 0°, 15°, and 45°), the flicker prevention performance and contrast are improved.
[0096] This invention provides an anisotropic light diffusion film 3, which, even when used in curved displays or curved windows at temperatures ranging from -15°C to 60°C, will not develop cracks or wrinkles. Therefore, the loss tangent of the anisotropic light diffusion layer 30 at temperatures ranging from -15°C to 60°C is preferably 0.07 to 0.8.
[0097] By making the loss angle tangent within the aforementioned range, even when used at temperatures ranging from -15°C to 60°C in displays or windows that require bending, there is a tendency to further suppress the occurrence of anisotropic light diffusion film 3 abnormalities such as cracks and wrinkles.
[0098] The loss tangent (tanδ) can be determined together with the storage modulus (E') and loss modulus (E") by dynamic viscoelasticity measurement (DMA).
[0099] The energy storage modulus and loss modulus of the anisotropic light diffusion layer 30 at temperatures ranging from -15°C to 60°C can be exemplified by the following numerical ranges.
[0100] The preferred energy storage modulus of the anisotropic light diffusion layer 30 at -15°C is 1.0 × 10⁻⁶. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7 Pa ~ 2.0 × 10 9 Pa.
[0101] The preferred energy storage modulus of the anisotropic light diffusion layer 30 at 25°C is 1.0 × 10⁻⁶. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7Pa ~ 2.0 × 10 9 Pa.
[0102] The preferred energy storage modulus of the anisotropic light diffusion layer 30 at 60°C is 1.0 × 10⁻⁶. 6 Pa ~ 2.0 × 10 8 Pa and loss modulus are 1.0 × 10 6 Pa ~ 2.0 × 10 8 Pa.
[0103] By setting the storage modulus of the anisotropic light diffusion layer 30 to the aforementioned range, even when used in displays or windows requiring bending at temperatures ranging from -15°C to 60°C, there is a tendency to further suppress the occurrence of cracks in the anisotropic light diffusion film 3. Furthermore, by setting the loss modulus of the anisotropic light diffusion layer 30 to the aforementioned range, even when used in displays or windows requiring bending at temperatures ranging from -15°C to 60°C, there is a tendency to further suppress the occurrence of wrinkles in the anisotropic light diffusion film 3.
[0104] The peak temperature of the lowest temperature side of the loss tangent of the anisotropic light diffusion layer 30 is preferably below 0°C, more preferably below -10°C, and even more preferably below -30°C.
[0105] By making the loss tangent of the anisotropic light diffusion layer 30 within the aforementioned range, even when used below 0°C in displays or windows that require bending, there is a tendency to further suppress the occurrence of cracks in the anisotropic light diffusion film 3.
[0106] The anisotropic light diffusion layer 30 is typically composed of a cured product of a composition containing a photopolymerizable compound. During the curing of this composition layer, regions with different refractive indices are formed. The composition containing the photopolymerizable compound will be described in detail later.
[0107] The thickness of the anisotropic light diffusion film 3 is preferably 10 μm to 60 μm. If the thickness is above the lower limit, the anisotropic light diffusion film 3 is difficult to break. If the thickness is below the upper limit, the anisotropic light diffusion film 3 is easy to bend. The thickness is measured, for example, by a method having the following steps (1) to (3).
[0108] (1) Use a slicer to form a cross section of the membrane and observe the cross section using an optical microscope.
[0109] (2) On the cross section, the length of the membrane surface and the opposite side of the membrane surface is measured at 10 locations in a direction perpendicular to the membrane plane (thickness direction).
[0110] (3) The average value of the measured values obtained from the 10 locations is taken as the thickness of the anisotropic light diffusion film 3.
[0111] (Anti-glare layer)
[0112] As the anti-glare layer 1, as long as the first surface 1a is uneven, it can be appropriately selected from known anti-glare layers. For example, a layer containing transparent resin can be used as the anti-glare layer 1.
[0113] The total light transmittance (JIS K 7361-1:1997) of the transparent resin is preferably 80% or more, and more preferably 90% or more.
[0114] Examples of transparent resins include thermoplastic resins and cured products of curable resins. Examples of curable resins include thermosetting resins and light-curing resins.
[0115] Thermoplastic resins used in the transparent resin of the anti-glare layer 1 include, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polymethyl methacrylate (PMMA), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), cyclic olefin copolymer (COC), norbornene resin, polyethersulfone, etc.
[0116] Examples of thermosetting resins used in the transparent resin of the anti-glare layer 1 include phenolic resin, furan resin, xylene-formaldehyde resin, ketone-formaldehyde resin, urea resin, melamine resin, aniline resin, alkyd resin, unsaturated polyester resin, and epoxy resin. These resins can be used alone or in combination.
[0117] The light-curing resin used as the transparent resin of the anti-glare layer 1 can be, for example, a monomer, oligomer, or prepolymer having free radical polymerizable functional groups such as acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, epoxy, vinyl ether, oxetane, or a suitable mixture of two or more.
[0118] Monomers used as photocurable resins include, for example, methyl acrylate, methyl methacrylate, methoxy polyethylene glycol methacrylate, cyclohexyl methacrylate, phenoxyethyl methacrylate, ethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, trimethylolpropane trimethacrylate, and polyurethane acrylates. They can be used alone or in combination.
[0119] Examples of oligomers and prepolymers of photocurable resins include polyester acrylates, polyurethane acrylates, multifunctional polyurethane acrylates, epoxy acrylates, polyether acrylates, alkyd acrylates, melamine acrylates, silicone acrylates, and other acrylate compounds; unsaturated polyesters; tetramethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether; various alicyclic epoxides and other epoxy compounds; oxetane compounds such as 3-ethyl-3-hydroxymethyloxetane, 1,4-bis{[(3-ethyl-3-oxetane)methoxy]methyl}benzene, and di[1-ethyl(3-oxetane)]methyl ether. These can be used alone or in combination.
[0120] The aforementioned photocurable resin, when subjected to UV-based photocuring, is used in conjunction with a photopolymerization initiator as a photocurable resin composition comprising the photocurable resin and the photopolymerization initiator.
[0121] The light used in photocuring can be any of ultraviolet, visible, or infrared light. Furthermore, this light can be polarized or unpolarized.
[0122] As photopolymerization initiators, they can be used alone or in appropriate combinations with free radical polymerization initiators such as acetophenone, benzophenone, thioxanone, benzoin, and benzoin methyl ether, as well as cationic polymerization initiators such as aromatic diazonium salts, aromatic sulfonium salts, aromatic iodonium salts, and metallocene compounds.
[0123] Within the limits that do not impede the polymerization and curing of the photocurable resin, the photocurable resin composition may also contain a polymeric resin. This polymeric resin is typically a thermoplastic resin, and specifically, examples include acrylic resins, alkyd resins, and polyester resins. These resins preferably have acidic functional groups such as carboxyl groups, phosphate groups, and sulfonic acid groups.
[0124] Alternatively, when using a light-curing resin composition to form the anti-glare layer, a coating comprising the light-curing resin composition and an organic solvent may also be used. After applying the coating and allowing the organic solvent to evaporate, it is light-cured, thereby forming a layer containing a transparent resin. As the organic solvent, an organic solvent suitable for dissolving the light-curing resin composition is appropriately selected. Specifically, considering coating adaptability to the light-transmitting substrate, such as wettability, viscosity, and drying speed, single or mixed solvents selected from alcohols, esters, ketones, ethers, and aromatic hydrocarbons can be used.
[0125] The particles can also be dispersed in a transparent resin. The particle size is not limited as long as it is sufficient to form the first surface 1a of the anti-glare layer 1 into an uneven surface. Furthermore, by using particles of a material with a refractive index different from that of the transparent resin (scattering particles), the anti-glare layer 1 can be endowed with internal scattering properties. Additionally, the method of making the first surface 1a of the anti-glare layer 1 uneven is not limited to using particles; known methods such as embossing can also be employed.
[0126] Examples of particles include cross-linked polymer particles of methyl methacrylate or polystyrene, and silica particles.
[0127] Additives can also be added to the transparent resin. Examples of additives include leveling agents, ultraviolet (UV) absorbers, antistatic agents, and thickeners. Leveling agents achieve uniform surface tension of the coating film formed from a paint containing a transparent resin or its precursor (such as a curing resin) and an organic solvent, and repair defects before the anti-glare layer forms. They are substances with lower interfacial tension and surface tension than the transparent resin or its precursor. Thickeners impart thixotropic properties to the aforementioned coating, preventing the sedimentation of particles and facilitating the formation of fine, uneven textures on the surface of the anti-glare layer.
[0128] The arithmetic mean roughness (Ra) of the first surface 1a (uneven surface) of the anti-glare layer 1 is preferably 0.05 μm to 1.00 μm, more preferably 0.10 μm to 0.80 μm, and even more preferably 0.15 μm to 0.50 μm. If Ra is above the lower limit, the anti-glare performance is better. If Ra is below the upper limit, the haze of the display film 10 is low, and therefore the image clarity is better.
[0129] Ra was determined according to JIS B0601:2013.
[0130] The internal haze of the anti-glare layer 1 is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. Internal haze is the haze caused by internal scattering from the anti-glare layer 1. If the internal haze is below the aforementioned upper limit, image clarity and black level / contrast are superior.
[0131] The internal haze was measured using a haze meter according to JIS K7136-1:2000.
[0132] The internal haze of the anti-glare layer 1 can be adjusted, for example, by the proportion of scattering particles (the matrix (resin constituting the layer) and particles with different refractive indices of 0.03 or higher) and the types of scattering particles within the anti-glare layer 1. The lower the proportion of scattering particles or the smaller the difference between the refractive index of the scattering particles and the refractive index of the matrix, the lower the internal haze tends to be.
[0133] The content of scattering particles in the anti-glare layer 1 is preferably 30 parts by weight or less relative to the resin constituting the layer, or it can be 0 parts by weight.
[0134] The thickness of the anti-glare layer 1 is preferably 1 to 25 μm, more preferably 2 to 10 μm, and even more preferably 3 to 7 μm.
[0135] If the thickness of the anti-glare layer 1 is above the lower limit value, the anti-glare performance is even better. Furthermore, when the anti-glare layer 1 is a layer formed of a photocurable resin composition, by making the thickness of the anti-glare layer 1 above the lower limit value, it is difficult for poor curing to occur during photocuring, and the anti-glare layer 1 has excellent wear resistance.
[0136] If the thickness of the anti-glare layer 1 is below the aforementioned upper limit, the image clarity is superior. Furthermore, when the anti-glare layer 1 is a layer formed from a photocurable resin composition, it is less likely to cause defects due to curing shrinkage (such as curling, microcracks, and reduced adhesion to the light-transmitting substrate). Consequently, it is possible to suppress the cost increase caused by the increased amount of coating required along with the increased film thickness.
[0137] (Translucent substrate)
[0138] The light-transmitting substrate 5 functions as a support for the anti-glare layer 1.
[0139] As for the light-transmitting matrix 5, the higher the transparency, the better.
[0140] The total light transmittance of the light-transmitting substrate 5 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the light-transmitting substrate 5 is, for example, 100% or less.
[0141] The total light transmittance of the light-transmitting substrate 5 was measured using a haze meter according to JIS K7361-1:1997.
[0142] The haze of the light-transmitting substrate 5 is preferably 3.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less. The haze of the light-transmitting substrate 5 is, for example, 0% or more.
[0143] The haze of the light-transmitting substrate 5 was measured using a haze meter according to JIS K7136-1:2000.
[0144] As for the light-transmitting substrate 5, there are no particular limitations as long as it is light-transmitting; examples include quartz glass or soda glass; and resin films such as polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polymethyl methacrylate (PMMA), polycarbonate (PC), polyimide (PI), polyethylene (PE), polypropylene (PP), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), cyclic olefin copolymer (COC), norbornene resin, polyethersulfone (PES), cellophane, and aromatic polyamide. Furthermore, when the display film 10 is used in a display, PET or TAC films are preferred.
[0145] The light-transmitting substrate 5 can also be a polarizing plate. As an example of a polarizing plate, one can cite a polarizing plate in which a polarizing element (e.g., a PVA film) is sandwiched between a pair of protective layers (e.g., a TAC film).
[0146] From the perspective of lightweighting, the thickness of the light-transmitting substrate 5 is preferably thinner, but considering its productivity and operability, it is preferably 1μm to 5mm, more preferably 10 to 500μm, and even more preferably 25 to 150μm.
[0147] To improve the adhesion with the anti-glare layer 1 or the transparent adhesive layer 7, the surface of the light-transmitting substrate 5 can also be subjected to surface treatments such as alkali treatment, plasma treatment, corona treatment, sputtering treatment, saponification treatment, coating with surfactants, silane coupling agents, or Si vapor deposition, etc.
[0148] (Transparent adhesive layer)
[0149] As for the transparent adhesive layer 7, there are no particular limitations, and any known transparent adhesive layer such as OCA (Optically Transparent Adhesive) can be used.
[0150] The transparent adhesive layer 7 generally contains a base resin, and may also contain any other components as needed. Examples of base resins for the transparent adhesive layer 7 include polyester resins, epoxy resins, polyurethane resins, silicone resins, and acrylic resins. Acrylic resins are preferred due to their high optical transparency and relatively low cost.
[0151] The total light transmittance of the transparent adhesive layer 7 is preferably 60% or more, more preferably 80% or more, and even more preferably 90% or more. For example, the total light transmittance of the transparent adhesive layer 7 is 100% or less.
[0152] The total light transmittance of the transparent adhesive layer 7 was measured using a haze meter according to JIS K7361-1:1997.
[0153] [Manufacturing method of film for display]
[0154] There are no particular limitations on the manufacturing method of the film 10 for display, but for example, manufacturing methods having the following steps (i) to (ii) can be cited.
[0155] (i) The process of manufacturing the anisotropic light diffusion film 3.
[0156] (ii) A process of bonding the surface of the anti-glare layer laminate 9, on the side of the light-transmitting substrate 5 where the anti-glare layer 1 is formed on one side of the light-transmitting substrate 5, and the anisotropic light diffusion film 3 via a transparent adhesive layer 7.
[0157] (Process (i))
[0158] Anisotropic light diffusion film 3 can be fabricated by, for example, referring to the methods disclosed in International Publications No. 2021 / 187555, No. 2022 / 044598, and No. 2022 / 138390. The anisotropic light diffusion film is coated onto a suitable substrate such as a transparent PET film using a composition (the composition used to manufacture the anisotropic light diffusion film 3, hereinafter sometimes referred to as a "photocurable resin composition" or "composition") to form a sheet, and an uncured resin composition layer is formed. After drying the uncured resin composition layer to evaporate the solvent as needed, light is irradiated onto the uncured resin composition layer, thereby producing the anisotropic light diffusion film 3.
[0159] The manufacturing method of the present invention mainly includes the following steps.
[0160] (1) Step 1-1: Step of applying an uncured resin composition layer onto a substrate
[0161] (2) Process 1-2: Process of obtaining parallel light from the light source
[0162] (3) Any process 1-3: The process of obtaining directional light.
[0163] (4) Steps 1-4: Steps to cure the uncured resin composition layer
[0164] <<<Compositions for Anisotropic Light Diffusion Films>>>
[0165] <<Ingredients>>
[0166] The anisotropic light diffusion film composition of the present invention comprises component (A) as a photopolymerizable compound. Furthermore, the anisotropic light diffusion film composition comprises component (B) as a photopolymerization initiator. Moreover, the anisotropic light diffusion film composition comprises component (C) as at least one plasticizer selected from ester-based, epoxy-based, and liquid rubber-based plastics.
[0167] Furthermore, the anisotropic light diffusion film composition preferably includes component (D) as a thermoplastic polymer. Additionally, the anisotropic light diffusion film composition preferably includes component (E) as a polymerization inhibitor. Furthermore, the anisotropic light diffusion film composition may also include component (F) as other components.
[0168] The following is a description of each component.
[0169] In the following description, where the upper limit and lower limit are described separately, all combinations of the upper limit and lower limit are described in this specification.
[0170] In this invention, the refractive index of each component is expressed as the refractive index determined according to the method of JIS K0062.
[0171] <(A) Component: Photopolymerizable compound>
[0172] Examples of photopolymerizable compounds that can be included as component (A) are compounds with functional groups such as acryloyl, methacryloyl, and allyl that have unsaturated double bonds and are capable of free radical polymerization (macromonomers, polymers, oligomers, monomers, etc.).
[0173] Compounds with functional groups exhibiting free radical polymerization (free radical polymerizable compounds) include those containing one or more unsaturated double bonds in their molecules. These compounds can be used individually or in mixtures. Methacrylates can also be used in the same way, but acrylates are generally preferred because they exhibit faster photopolymerization rates compared to methacrylates.
[0174] Component (A) is preferably composed of (meth)acrylates, particularly preferably of a first (meth)acrylate having multiple aromatic rings and one (only one) (meth)acryloyl group, and a second (meth)acrylate as a component different from the first (meth)acrylate, i.e., as component (b1) and / or component (b2). Furthermore, the second (meth)acrylate may be either component (b1) or component (b2), or may include both components (b1) and (b2).
[0175] Furthermore, when component (A) is composed of (meth)acrylate, component (A) may also arbitrarily contain a third (meth)acrylate or other (meth)acrylate having one or more fluorene skeletons and (meth)acryloyl groups respectively.
[0176] (First (meth)acrylate)
[0177] The first (meth)acrylate preferably has a biphenyl ring structure or a diphenyl ether structure as a structure containing multiple aromatic rings. Such a biphenyl or diphenyl ether structure can be present in the skeleton as one or more. Having such a structure results in a (meth)acrylate with a very high refractive index.
[0178] The first (meth)acrylate is typically a high refractive index material. Specifically, the refractive index of the first (meth)acrylate is preferably 1.50 or higher, more preferably 1.53 or higher, and even more preferably 1.56 or higher. There is no particular limitation on the upper limit of the refractive index; for example, it is preferably 1.70 or lower, more preferably 1.65 or lower, and even more preferably 1.60 or lower. By making the refractive index of the first (meth)acrylate within such a range, the diffusivity of the anisotropic light diffusion film can be further improved.
[0179] There are no particular limitations on such first (meth)acrylates; examples include biphenyl compounds represented by the following general formula (1), or diphenyl ether compounds represented by the following general formula (2).
[0180]
[0181] In general formula (1), R 1 ~R 10 Independently, R 1 ~R 10 Any one of them is a substituent represented by the following general formula (3) or (4). The remaining part may be any substituent other than (meth)acryloyl group, specifically, substituents such as hydrogen atom, hydroxyl group, carboxyl group, alkyl group, alkoxy group, haloalkyl group, hydroxyalkyl group, carboxylalkyl group and halogen atom may be included.
[0182] Furthermore, in general formula (2), R 11 ~R 20 Independently, R 11 ~R 20 Any one of them is a substituent represented by the following general formula (3) or (4). The remaining part may be any substituent other than (meth)acryloyl group, specifically, substituents such as hydrogen atom, hydroxyl group, carboxyl group, alkyl group, alkoxy group, haloalkyl group, hydroxyalkyl group, carboxylalkyl group and halogen atom may be included.
[0183]
[0184] (In general formula (3), R) 21 (The carbon atom n is a hydrogen atom or a methyl group, the number of carbon atoms n is an integer from 1 to 4, and the repetition number m is an integer from 1 to 10.)
[0185] (In general formula (4), R) 22 (The carbon atom n is a hydrogen atom or a methyl group, the number of carbon atoms n is an integer from 1 to 4, and the repetition number m is an integer from 1 to 10.)
[0186] The number of repetitions m in the substituents represented by the above general formulas (3) and (4) is usually preferably an integer from 1 to 10.
[0187] The reason is that if the repetition number m is greater than 10, the refractive index enhancement effect of the first (meth)acrylate from the aromatic ring is suppressed, and sometimes the diffusivity of the anisotropic light diffusion film is reduced.
[0188] Therefore, the number of repetitions m in the substituents represented by general formulas (3) and (4) is more preferably an integer of 1 to 4, and even more preferably an integer of 1 to 2.
[0189] Furthermore, from the same point of view, the number of carbon atoms n in the substituents represented by general formulas (3) and (4) is generally preferably an integer from 1 to 4, and more preferably an integer from 1 to 2.
[0190] As a specific example of a biphenyl compound represented by the above general formula (1), a compound represented by the following formula (5) can be preferably listed.
[0191]
[0192] As a specific example of a diphenyl ether compound represented by the above general formula (2), a compound represented by the following formula (6) can be preferably cited.
[0193]
[0194] The first (meth)acrylate may contain only one of the above-described ingredients, or it may contain multiple of the above-described ingredients.
[0195] (Viscosity of the first (meth)acrylate)
[0196] The viscosity of the first (meth)acrylate at 25°C is preferably 1000 mPa·s or less, more preferably 500 mPa·s or less, and even more preferably 100 mPa·s or less. The lower limit of viscosity is not particularly limited, for example, it is 1 mPa·s.
[0197] By using the viscosity of the first (meth)acrylate at 25°C within these ranges, the fluidity of the composition is improved when the components in component (A) are used in combination, thus promoting phase separation of the components during curing and improving the diffusion performance of the resulting anisotropic light diffusion film.
[0198] (Second (meth)acrylate)
[0199] The second (meth)acrylate is a component different from the first (meth)acrylate, and is component (b1) and / or component (b2). Alternatively, the second (meth)acrylate may be either component (b1) or component (b2), or both component (b1) and component (b2).
[0200] (b1) The component is a (meth)acrylate having multiple (meth)acryloyl groups.
[0201] (b1) The number of (meth)acryloyl groups in the component is not particularly limited. In order to improve the flexibility of the anisotropic light diffusion film after photocuring, it can be 2 to 3. In order to improve the rigidity and heat resistance after photocuring, it can be 4 to 6.
[0202] As a component (b1), there are no particular limitations, for example, pentaerythritol tetraacrylate represented by the following general formula (7) can be cited.
[0203]
[0204] When the second (meth)acrylate contains component (b1), the first (meth)acrylate may also be free of hydroxyl, carboxyl, and amino groups.
[0205] (b2) The component is a (meth)acrylate having one or more hydroxyl, carboxyl, or amino groups and one (only one) (meth)acryloyl group. Alternatively, (b2) may have two or more hydroxyl, carboxyl, or amino groups. In this case, it may have two or more of the same type of functional group (e.g., two or more hydroxyl groups), or it may have a total of two or more different types of functional groups (e.g., one or more hydroxyl groups and one or more carboxyl groups).
[0206] As a component (b2), there are no particular limitations, for example, (meth)acrylates represented by the following general formula (8) can be cited.
[0207]
[0208] (In general formula (8), R) 25 R is a hydrogen atom or a methyl group. 26 R is any one of hydroxyl, carboxyl, or amino groups. 27 (It can be any one of the following substituents: hydrogen atom, hydroxyl group, carboxyl group, alkyl group, alkoxy group, haloalkyl group, hydroxyalkyl group, carboxyalkyl group, and halogen atom.)
[0209] The substituent R represented by the above general formula (8) 26Typically, it is any one of hydroxyl, carboxyl, or amino groups. The reason is that by having the aforementioned functional group act as both a "hydrogen bond donor" and a "hydrogen bond acceptor," hydrogen bonds are generated in the molecular structure of the anisotropic light-diffusing film after photocuring, thus creating a complex three-dimensional structure and weakening the π-π stacking interactions between the aromatic rings from the first (meth)acrylate. Therefore, to enhance the effect of the aforementioned hydrogen bonds, it is more preferable to have the functional group R... 26 It is a hydroxyl group.
[0210] In addition, substituent R 27 Typically, the preferred substituents are hydrogen atoms, hydroxyl groups, carboxyl groups, alkyl groups, alkoxy groups, haloalkyl groups, hydroxyalkyl groups, carboxyalkyl groups, and halogen atoms. In order to improve the refractive index, alkoxy groups having an aromatic ring are more preferred.
[0211] As a specific example of (meth)acrylate represented by the above general formula (8), a compound represented by the following formula (9) can be preferably cited.
[0212]
[0213] The second (meth)acrylate is preferably a high refractive index material. The value of the refractive index is not particularly limited, but specifically, it is preferably 1.44 or higher, more preferably 1.48 or higher, and even more preferably 1.52 or higher. As for the upper limit of the refractive index, it is not particularly limited, for example, it is preferably 1.57 or lower. By making the refractive index of the second (meth)acrylate within such a range, the diffusivity of the anisotropic light diffusion film can be further improved.
[0214] As described above, the second (meth)acrylate is a high refractive index material, and therefore preferably has an aromatic ring structure.
[0215] The second (meth)acrylate may contain only one of the above-mentioned components or may contain multiple of the above-mentioned components.
[0216] In the fabrication of anisotropic light diffusion films, increasing the refractive index difference between high-refractive-index and low-refractive-index materials can make the structural boundaries more pronounced and improve diffusivity. First (meth)acrylate can be considered useful as a high-refractive-index polymerizable compound, but it undergoes π-π stacking interactions. As mentioned above, hue can be attributed to these π-π stacking interactions.
[0217] Therefore, by using component (b1) as the second (meth)acrylate, and utilizing the multiple (meth)acryloyl groups contained in component (b1), the structure of the anisotropic light diffusion film composition after photocuring becomes a complex three-dimensional structure, making it difficult to generate π-π stacking interactions between aromatic rings.
[0218] Furthermore, by using component (b2) as the second (meth)acrylate, component (b2) possesses functional groups that function as both a "hydrogen bond donor" and a "hydrogen bond acceptor." Thus, by incorporating hydrogen bonds into the molecular structure of the anisotropic light diffusion film after photocuring of the composition, a complex three-dimensional structure is formed, making it difficult for π-π stacking interactions between aromatic rings to occur. Hydroxyl, carboxyl, and amino groups are used as functional groups to achieve this effect.
[0219] (Third (meth)acrylate)
[0220] The third (meth)acrylate is a (meth)acrylate having one or more fluorene skeletons and (meth)acryloyl groups, and is an arbitrary component.
[0221] The third (meth)acrylate may contain one or more aromatic rings (aromatic ring groups / aromatic ring-containing groups) as substituents of the fluorene skeleton, preferably containing two or more aromatic rings as substituents of the fluorene skeleton. There is no particular upper limit to the number of aromatic rings that are substituents of the fluorene skeleton contained in the third (meth)acrylate, but for example, it is preferably 10 or less.
[0222] The number of (meth)acryloyl groups contained in the third (meth)acrylate is not particularly limited, and can be 1 or 2 or more, preferably containing multiple (meth)acryloyl groups. Furthermore, as an upper limit, there is no particular limitation, but 8 or less is preferred.
[0223] As a third (meth)acrylate containing two or more aromatic rings as substituents of the fluorene skeleton, specifically, compounds represented by the following formula (10) can be exemplified.
[0224]
[0225] In the above equation (10), R A and R C Each is independently a substituent containing a (meth)acryloyl group, preferably a (meth)acryloyloxy group (which may also undergo ethylene oxide (EO) addition or propylene oxide (PO) addition with a repeating number of 1 to 5). Furthermore, R B and R D Each is an aliphatic substituent consisting of 1 to 6 hydrogen atoms or carbon atoms.
[0226] As a third (meth)acrylate, more specifically, compounds represented by formulas (11) to (13) can be exemplified.
[0227]
[0228] Tertiary (meth)acrylates can be commercially available. Examples of commercially available tertiary (meth)acrylates include "A-BPEF-2" (9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., and "OGSOL EA-0200", "OGSOL EA-0300", "OGSOL EA-5060GP", and "OGSOL GA-2800" manufactured by Osaka Gas Chemical Co., Ltd.
[0229] The refractive index of the third (meth)acrylate is preferably 1.50 or higher, more preferably 1.53 or higher, and even more preferably 1.56 or higher. There is no particular limitation on the upper limit of the refractive index; for example, it is preferably 1.70 or lower. By making the refractive index of the third (meth)acrylate within such a range, the diffusivity of the anisotropic light diffusion film can be further improved.
[0230] Third (meth)acrylate may contain only one of the above-mentioned components or may contain multiple of the above-mentioned components.
[0231] (Other (meth)acrylates)
[0232] Without impairing the effects of the invention, component (A) may also contain other methacrylates besides the first to third methacrylates (other methacrylates commonly used in optical film compositions).
[0233] (A) Viscosity of component A)
[0234] In this invention, the viscosity of component (A) as a whole at 25°C is preferably 10,000 mPa·s or less, more preferably 5,000 mPa·s or less, even more preferably 3,000 mPa·s or less, and particularly preferably 1,000 mPa·s or less. Furthermore, the viscosity of component (A) as a whole at 25°C is most preferably 500 mPa·s or less, 250 mPa·s or less, or 100 mPa·s or less. The lower limit of viscosity is not particularly limited, for example, it is 1 mPa·s.
[0235] By making the viscosity of component (A) as a whole at 25°C within these ranges, the fluidity of the composition is improved when the components in component (A) are used in combination, thus promoting phase separation of the components during curing and improving the diffusion performance of the resulting anisotropic light diffusion film.
[0236] <(B) Component: Photopolymerization Initiator>
[0237] (B) The photopolymerization initiator is a compound that generates free radicals by irradiating active energy rays such as ultraviolet light, and conventionally known initiators can be used.
[0238] Examples of photopolymerization initiators include benzophenone, benzyl, michidone, 2-chlorothioxanthone, 2,4-diethylthioxanthraphenone, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-diethoxyacetophenone, benzyl dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, and 2-methyl- 1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(pyrrolo-1-yl)phenyl]titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. These compounds can be used individually or in combination.
[0239] Photopolymerization initiators can usually be used by directly dissolving powders in photopolymerizable compounds. However, in cases of poor solubility, photopolymerization initiators that have been pre-dissolved in a solvent can also be used.
[0240] <(C) Component: At least one plasticizer selected from ester-based, epoxy-based, and liquid rubber-based plasticizers>
[0241] In order to provide an anisotropic light diffusion film that does not crack, wrinkle or other abnormalities even when used at temperatures ranging from -15°C to 60°C, and a display film and display using the anisotropic light diffusion film, the photocurable resin composition comprises at least one plasticizer from the group consisting of ester-based, epoxy-based and liquid rubber-based materials.
[0242] The plasticizer can be either a photocurable plasticizer or a thermocurable plasticizer. When the plasticizer is a thermocurable compound, from a curing point of view, the photocurable resin composition preferably also includes a curing agent. In this case, the anisotropic light diffusion layer is composed of light and thermal polymerization incorporated into the photopolymerization process.
[0243] Examples of ester-based plasticizers include fatty acid esters such as stearates and oleates; dicarboxylic acid esters such as maleate diester, fumarate diester, adipate diester, sebacic acid diester, phthalate diester, isophthalate diester, and terephthalate diester; triphosphate esters; and polyesters such as adipic acid polyester. Examples of ester groups used in ester-based plasticizers include alkyl ester groups such as butyl, pentyl, hexyl, octyl, isooctyl, and decyl, and aryl ester groups such as toluene.
[0244] Examples of epoxy plasticizers include epoxidized soybean oil and epoxidized flaxseed oil.
[0245] Examples of liquid rubbers include homopolymers or copolymers of polyisoprene, homopolymers or copolymers of polybutadiene, copolymers of isoprene and butadiene, and poly-styrene-butadiene. Liquid rubbers can also be acid-modified compounds based on unsaturated carboxylic acids such as maleic anhydride and maleic acid. Photopolymerizable functional groups such as acrylic groups can also be introduced into liquid rubbers to impart photocurability.
[0246] <(D) Composition: Thermoplastic polymer>
[0247] The composition for anisotropic light diffusion film preferably contains component (D) as a thermoplastic polymer.
[0248] (D) The glass transition temperature of the component is preferably -40°C or higher, more preferably 0°C or higher, and even more preferably 30°C or higher. There is no particular limitation on the upper limit of the glass transition temperature, but it is preferably 150°C or lower.
[0249] The glass transition temperature can be determined by a known method, such as JIS K7121-1987 "Method for determination of transition temperature of plastics".
[0250] (D) The weight-average molecular weight of component D is preferably 1,000 to 500,000, more preferably 10,000 to 400,000, and even more preferably 50,000 to 300,000.
[0251] Weight-average molecular weight can be determined using well-known methods, such as gel permeation chromatography (GPC) as a conversion of molecular weight to polystyrene.
[0252] By setting the glass transition temperature and weight-average molecular weight of component (D) within the aforementioned range, compatibility with component (A) can be improved, resulting in an anisotropic light diffusion film with excellent performance. This improves durability in heat resistance tests and allows the anisotropic light diffusion film before UV curing to have a suitable elastic modulus for storage under winding.
[0253] Component (D) is typically a low refractive index material. Specifically, the refractive index of component (D) is preferably less than 1.55, more preferably less than 1.50, and even more preferably less than 1.48. There is no particular limitation on the lower limit of the refractive index, but it is preferably 1.35 or higher, and more preferably 1.40 or higher.
[0254] The difference (nA-nC) between the refractive index nA of component (A) and the refractive index nC of component (D) is preferably 0.01 to 0.3, more preferably 0.03 to 0.3, and particularly preferably 0.05 to 0.3.
[0255] There are no particular limitations on such component (D), and examples include acrylic resin, styrene resin, styrene-acrylic acid copolymer, polyurethane resin, polyester resin, epoxy resin, cellulose resin, silicone resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral resin, polyvinyl alcohol resin, polyvinyl formal resin, polyvinyl alcohol acetal resin, polyvinylidene fluoride, polymethyl methacrylate (PMMA)-polybutyl acrylate (PBA) block copolymer, polyvinylidene fluoride (PVDF)-hexafluoropropylene (HFP) copolymer, etc.
[0256] (D) The component is particularly preferred to be a polyurethane (meth)acrylate composed of a cyclic aliphatic compound having two isocyanate groups, a polyol compound, or a hydroxyalkyl (meth)acrylate.
[0257] Examples of cyclic aliphatic compounds having two isocyanate groups include isophorone diisocyanate (IPDI) and hydrogenated diphenylmethane diisocyanate.
[0258] As a polyol compound, a diol compound is preferred, and polyalkylene glycols are particularly preferred. Specifically, examples include polyethylene glycol, polypropylene glycol, polybutane glycol, and polyhexane glycol, with polypropylene glycol being preferred.
[0259] Examples of hydroxyalkyl methacrylates include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxybutyl methacrylate, and 4-hydroxybutyl methacrylate.
[0260] (D) Components can be manufactured by synthesizing the above components using conventional methods.
[0261] In addition, there is no particular limitation on the proportion of each component. For example, a molar ratio of "cyclic aliphatic compound having two isocyanate groups": "polyol compound": "(meth)acrylate hydroxyalkyl ester" = 1 to 5: 1 to 1 to 5 is preferred.
[0262] (D) may contain only one of the above-mentioned components or may contain multiple of the above-mentioned components. In addition, if (D) is composed of multiple components, the refractive index of (B) only needs to be the average of their values.
[0263] By incorporating such a (D) component, phase separation based on the refractive index difference with that of a high-refractive-index material containing (A) component can be easily achieved. Furthermore, it is difficult to form indentations when fabricating anisotropic light diffusion films, and anisotropic light diffusion films with excellent storage properties can be fabricated.
[0264] <(E) Component: Polymerization Inhibitor>
[0265] (E) is a polymerization inhibitor having a structure in which a carbonyl or hydroxyl group is added as a substituent in a conjugated cyclic compound.
[0266] Examples of polymerization inhibitors with the above-mentioned structure include so-called quinone-based and phenol-based polymerization inhibitors.
[0267] Specifically, component (E) is preferably one or more compounds selected from the group consisting of compounds represented by the following chemical formulas (E1) to (E6).
[0268]
[0269] In formulas (E1) to (E6), R1 to R5 are each independently a hydrogen atom, a halogen atom, a carboxyl group, or a C1 to C4 (preferably C1 to C3) alkoxy group (e.g., methoxy, ethoxy, propoxy) or alkyl group (e.g., methyl, ethyl, propyl, or tert-butyl).
[0270] Thus, component (E) is preferably a polymerization inhibitor based on hydroquinone (e.g., formula (E1) above), quinone methylation (e.g., formulas (E2) and (E4) above), benzoquinone (e.g., formula (E3) above), phenol (e.g., formula (E5) above), or catechol (e.g., formula (E6) above). Furthermore, component (E) is more preferably a polymerization inhibitor based on hydroquinone, quinone methylation, or benzoquinone, and particularly preferably a polymerization inhibitor based on benzoquinone.
[0271] The polymerization inhibitor only needs to have a structure with a carbonyl or hydroxyl group added. Therefore, in addition to compounds represented by any one of the above formulas (E1) to (E6), polymerization inhibitors such as pyrogallol-based and naphthoquinone-based inhibitors can also be used.
[0272] In an anisotropic light diffusion film composition containing component (A) as a high refractive index material and a polymerization initiator, by further containing a predetermined polymerization inhibitor, the growth of the structural regions described later becomes appropriate, resulting in improved optical properties (especially diffusion width).
[0273] <(F) Ingredients: Other Ingredients>
[0274] As other components, i.e., component (F), the composition may also contain various known dyes or sensitizers, and other known additives, to improve photopolymerization properties, etc. Furthermore, the composition may also contain solvents, dispersion media, etc. These are arbitrary components and can be used alone or in combination, or omitted altogether.
[0275] Furthermore, a curing agent that can cure photopolymerizable compounds by heating can be used in combination with a photopolymerization initiator.
[0276] Solvents used in preparing compositions containing photopolymerizable compounds include, for example, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, xylene, etc.
[0277] Furthermore, if the acid-generating agent remains after the composition has cured, it could potentially have adverse effects on other components when used in devices such as displays. Therefore, it is preferable that the acid-generating agent is not included as another component. For example, the content of the acid-generating agent in the composition is preferably 1% or less.
[0278] <<Content>>
[0279] <(A) Ingredient>
[0280] (A) The content of the component relative to the total solid components of the composition (the total amount of non-volatile components after removing volatile solvents) is not particularly limited, but is preferably 30% by weight or more, 35% by weight or more, 40% by weight or more, or 45% by weight or more. The upper limit is not particularly limited, but may be, for example, 99% by weight, 95% by weight, 90% by weight, 85% by weight, 80% by weight, 70% by weight, or 60% by weight.
[0281] The content of the second (meth)acrylate is 50 to 1000 parts by weight relative to the content of the first (meth)acrylate, preferably 65 to 900 parts by weight, and more preferably 75 to 200 parts by weight.
[0282] The content of the third (meth)acrylate in the composition is 3 to 100 parts by weight when the content of other (A) components is set to 100 parts by weight, preferably 4 to 50 parts by weight, and more preferably 5 to 25 parts by weight.
[0283] The total content of the first to third (meth)acrylates relative to component (A) can be 50% by weight or more (preferably 70% by weight or more, 80% by weight or more, or 90% by weight or more).
[0284] <(B) Component>
[0285] The content of component (B) relative to the content of component (A) is preferably 0.1 to 20 parts by weight per 100 parts by weight, more preferably 0.1 to 15 parts by weight, and even more preferably 0.1 to 7 parts by weight.
[0286] <(C) Component>
[0287] The plasticizer in the anisotropic light diffusion film composition is preferably 30% by weight or less of the total anisotropic light diffusion film composition.
[0288] <(D) component>
[0289] The content of component (D) relative to the content of component (A) is preferably 10 to 400 parts by weight, more preferably 25 to 150 parts by weight, and even more preferably 40 to 100 parts by weight.
[0290] Furthermore, according to another viewpoint, the content of component (D) relative to the total amount of non-volatile components in the composition (excluding solvent and dispersion medium) is preferably 10 to 80% by weight, more preferably 15 to 70% by weight, and even more preferably 20 to 60% by weight.
[0291] <(E) component>
[0292] The content of component (E) in the composition is preferably 0.001 parts by weight to 1 part by weight when the total amount of non-volatile components in the composition is set to 100 parts by weight, more preferably 0.005 parts by weight to 0.5 parts by weight, more preferably 0.008 parts by weight to 0.1 parts by weight, and even more preferably 0.015 parts by weight to 0.05 parts by weight.
[0293] Furthermore, according to another viewpoint, the content of component (E) in the composition is preferably 0.001% to 0.5% by weight relative to the total amount of non-volatile components in the composition, more preferably 0.005% to 0.1% by weight, and even more preferably 0.01% to 0.04% by weight.
[0294] <Complex Ingredients>
[0295] The total proportion of component (A) and component (D) relative to the total solid components of the composition (excluding the total amount of non-volatile components) is not particularly limited, and may be, for example, 50% or more by weight, 60% or more by weight, 70% or more by weight, 80% or more by weight, 90% or more by weight, 95% or more by weight, 99% or more by weight, 100% or more by weight, etc.
[0296] By ensuring that the total proportions of components (A) and (D) in the composition are within the range described above, appropriate interactions between the components can be achieved.
[0297] Furthermore, in the composition, the ratio expressed as [content of component (E) / content of component (B)] is preferably 0.005 to 0.1, more preferably 0.01 to 0.05.
[0298] <Step 1-1: Step of applying an uncured resin composition layer onto the substrate>
[0299] The method involves applying a UV-curable resin composition as an uncured resin composition layer onto a substrate using conventional coating or printing methods. Specifically, this can be achieved using air knife coating, rod coating, doctor blade coating, scraper coating, reverse coating, conveyor roller coating, gravure roller coating, coincidence coating, casting coating, spray coating, slotted coating, calendering coating, baffle coating, dip coating, die coating, gravure printing (such as photogravure), screen printing, and other printing methods. When the composition has a low viscosity, a weir of a certain height can be formed around the substrate, and the composition can be poured into the portion enclosed by this weir.
[0300] In step 1-1, in order to prevent oxygen obstruction of the uncured resin composition layer, columnar regions characterized as anisotropic light diffusion films are effectively formed, and masks that are tightly sealed to the light irradiation side of the uncured resin composition layer can also be laminated to locally change the light irradiation intensity.
[0301] As the mask material, a light-absorbing filler such as carbon is dispersed in a matrix. A portion of the incident light is absorbed by the carbon, but the opening is preferably a structure that allows sufficient light transmission. Examples of such matrices include transparent plastics such as polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), acrylic resin, and polyethylene, as well as inorganic materials such as glass and quartz. The mask can be a patterned mask with a substrate containing these matrices for controlling the amount of ultraviolet light transmitted, or a mask containing ultraviolet-absorbing pigments in the matrix.
[0302] Without using such a mask, oxygen barrier of the uncured resin composition layer can be prevented by light irradiation under a nitrogen atmosphere. Furthermore, even simply laminating a conventional transparent film onto the uncured resin composition layer is effective in preventing oxygen barrier and promoting the formation of columnar regions. During light irradiation through such a mask or transparent film, a photopolymerization reaction corresponding to the irradiation intensity occurs in the composition containing the photopolymerizable compound, thus easily generating a refractive index distribution, which is effective in the fabrication of the anisotropic light diffusion film according to this method.
[0303] <Process 1-2: Process of obtaining parallel light rays from the light source>
[0304] As a light source, short-arc ultraviolet light is typically used. Specifically, high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, xenon lamps, etc., can be used. At this time, it is necessary to obtain light rays parallel to the desired scattering central axis. Such parallel light rays can be obtained, for example, by placing a point light source and an optical lens such as a Fresnel lens between the point light source and the uncured resin composition layer to illuminate the parallel light rays, or by placing a reflector behind the light source to emit light as a point light source in a predetermined direction.
[0305] <Any steps 1-3: Steps to obtain directional light>
[0306] Any step 1-3 is a step of incidenting parallel light rays onto a directional diffuser element to obtain directional light rays. Figure 5 as well as Figure 6 This is a schematic diagram illustrating a method for manufacturing anisotropic light diffusion film according to the present invention, including any of steps 1-3.
[0307] The directional diffusion elements 301 and 302 used in any of the steps 1-3 can be any elements that impart directionality to the parallel light ray D incident from the light source 300.
[0308] exist Figure 5 as well as Figure 6 The text describes how directional light E is incident on the uncured resin composition layer 303 in a manner that diffuses more extensively in the X direction and diffuses almost minimally in the Y direction. To obtain such directional light, for example, a method can be used where needle-shaped fillers with high aspect ratios are included in the directional diffusion elements 301 and 302, and these needle-shaped fillers are oriented such that they extend in the Y direction along their long axis. Besides using needle-shaped fillers, various other methods can be used for the directional diffusion elements 301 and 302.
[0309] Here, the aspect ratio of the directional light E is preferably 2 to 50. A columnar region with an aspect ratio that approximately corresponds to this aspect ratio is formed.
[0310] In any of steps 1-3, by adjusting the directional expansion of the light E, the size (aspect ratio, minor axis SA, major axis LA, etc.) of the formed columnar region can be appropriately determined. For example, in Figure 5 as well as Figure 6 Anisotropic light diffusion films of this method can be obtained from any of the following methods. Figure 5 and Figure 6 The difference is that the directional extension of light E is in Figure 5 The middle is relatively large, while Figure 6 The size of the columnar region varies depending on the extent of the directional light E.
[0311] The propagation of the directional light E depends primarily on the type of directional diffusion elements 301 and 302 and their distance from the uncured resin composition layer 303. As this distance decreases, the size of the columnar region decreases; as this distance increases, the size of the columnar region increases. Therefore, by adjusting this distance, the size of the columnar region can be adjusted.
[0312] <Steps 1-4: Steps to cure the uncured resin composition layer>
[0313] The light used to cure the uncured resin composition layer by irradiation needs to contain wavelengths capable of curing photopolymerizable compounds, typically light with a wavelength centered at 365 nm from a mercury lamp. When using this wavelength to fabricate anisotropic light-diffusing films, an illuminance of 0.01 mW / cm² is preferred. 2 ~100mW / cm 2 The range is more preferably 0.1 mW / cm 2 ~20mW / cm 2 This is because if the illuminance is less than 0.01 mW / cm² 2 If the curing time exceeds 100mW / cm, the production efficiency will decrease. 2 If the photopolymer compound cures too quickly, no structure will form, and the optical properties of the target cannot be expressed.
[0314] Furthermore, the irradiation time is not particularly limited, but is preferably 10 to 180 seconds, and more preferably 30 to 120 seconds. By irradiating with the above light, the anisotropic light diffusion film of this method can be obtained.
[0315] As described above, anisotropic light diffusion films are obtained by irradiating the uncured resin composition layer with low-intensity light for a relatively long period of time, forming a specific internal structure. Therefore, irradiation with only this light can sometimes leave unreacted monomer components, resulting in stickiness and causing problems with workability and durability. In such cases, additional irradiation at 1000 mW / cm² can be applied. 2 The above high-intensity light causes the residual monomers to polymerize. At this point, the light irradiation can also be performed from the opposite side of the side where the mask is stacked.
[0316] As described above, when curing the uncured resin composition layer, by adjusting the angle of the light irradiating the uncured resin composition layer, the scattering center axis of the resulting anisotropic light diffusion film can be made to be the desired scattering center axis.
[0317] In addition, anisotropic light diffusion films can also have other layers (adhesive layer, functional layer, transparent film layer, etc.).
[0318] (Process (ii))
[0319] In step (ii), the surface of the anti-glare layer laminate 9, on which the anti-glare layer 1 is formed, on one side of the light-transmitting substrate 5, is bonded to the anisotropic light diffusion film 3 obtained in step (i) via a transparent adhesive layer 7. Thus, a display film 10 is obtained.
[0320] As the anti-glare layer laminate 9, a commercially available anti-glare layer laminate or an anti-glare layer laminate manufactured by a known manufacturing method can be used. The anti-glare layer laminate 9 can be manufactured by forming an anti-glare layer 1 on one side of the light-transmitting substrate 5. The method for forming the anti-glare layer 1 is not particularly limited and can be a known method. For example, methods described in International Publication No. 2005 / 093468, International Publication No. 2008 / 093769, Japanese Patent Application Publication No. 2010-248451, Japanese Patent Application Publication No. 2011-013238, and Japanese Patent Application Publication No. 2010-256882 can be cited.
[0321] As the transparent adhesive layer 7, commercially available transparent adhesive sheets can be used. Alternatively, transparent adhesive sheets manufactured using known manufacturing methods can be used.
[0322] The above description illustrates the display film of the present invention through embodiments, but the present invention is not limited to the above embodiments. The structures and combinations thereof in the above embodiments are examples, and additions, omissions, substitutions, and other modifications to the structures can be made without departing from the spirit of the present invention.
[0323] For example, such as Figure 3 As shown in display film 11, it can also have a structure that does not have a light-transmitting substrate 5 and a transparent adhesive layer 7. Such a display film is obtained, for example, by forming an anti-glare layer directly on one side of an anisotropic light diffusion film 3.
[0324] like Figure 4 The display film 12 shown can also have a structure without a transparent adhesive layer 7.
[0325] Such a display film is obtained, for example, by directly forming an anisotropic light diffusion film 3 on the surface opposite to the anti-glare layer 1 side of the light-transmitting substrate 5.
[0326] The display film of the present invention may also include other layers besides the anti-glare layer 1, the anisotropic light diffusion film 3, the light-transmitting substrate 5, and the transparent adhesive layer 7. Examples of other layers include a phase retardation layer, a light reflection layer, and an optical control layer. Other layers may be disposed between the anti-glare layer 1 and the anisotropic light diffusion film 3, or on the side of the anisotropic light diffusion film 3 opposite to the side of the anti-glare layer 1.
[0327] 〔monitor〕
[0328] The display of the present invention includes the display film of the present invention.
[0329] Examples of displays include liquid crystal displays (LCDs), plasma display panels (PDPs), organic light-emitting diode (EL) displays, field emission displays (FEDs), rear projectors, cathode ray tube displays (CRTs), surface electric field displays (SEDs), and electronic paper.
[0330] The display of the present invention typically comprises a display body having a display surface and a display film of the present invention disposed on the display surface of the display body. In this case, the display film of the present invention is disposed with the anti-glare layer side facing the visual confirmation side (the side opposite to the display surface side). Preferably, the anti-glare layer is disposed on the most visual confirmation side in the thickness direction of the display film. The display film can be adhered to the display surface via a transparent adhesive layer or the like.
[0331] Example
[0332] The invention will now be described in more detail by way of examples and comparative examples, but the invention is not limited to these examples.
[0333] (Fabrication of anisotropic light diffusion film)
[0334] The anisotropic light diffusion film of the present invention and the anisotropic light diffusion film of the comparative example were fabricated according to the following method.
[0335] [Example 1]
[0336] 1. Preparation of Composition Solution No. 1 for Anisotropic Light Diffusion Films
[0337] The various materials shown below are mixed and stirred in the amounts shown below to obtain the anisotropic light diffusion film composition solution No. 1.
[0338] • (A) Composition: 100 parts by weight of ethylene oxide (EO) modified bisphenol A diacrylate (manufactured by Kyoei Chemical Co., Ltd., trade name: Light Acrylate (registered trademark) BP-4EAL, refractive index: 1.54 (25°C)).
[0339] (B) Composition: Polyvinyl acetate (PVAc) (Refractive index: 1.460, average molecular weight: 200,000, glass transition temperature: 40°C) 60 parts by weight
[0340] (C) Ingredients: Ester-based plasticizer (manufactured by DIC, trade name: Polycizer (registered trademark) W-230-H, viscosity: 220 mPa·s (25℃)) 20 parts by weight
[0341] (D) Ingredient: 2 parts by weight of 2,2-dimethoxy-2-phenylacetophenone
[0342] Solvent: 150 parts by weight of butyl acetate
[0343] 2. Fabrication of Composite Layer No. 1 for Anisotropic Light Diffusion Film
[0344] The anisotropic light diffusion film composition solution No. 1 obtained was applied to a 100 μm thick PET film (manufactured by Toyobo Co., Ltd., trade name: A4360) using a coater. The coating was then dried in a clean oven with the drying oven temperature set to 80°C, thereby obtaining an anisotropic light diffusion film composition layer No. 1 with a film thickness of 40 μm.
[0345] 3. Fabrication of Anisotropic Light Diffusion Film No. 1
[0346] Next, a polyvinyl alcohol film (hereinafter referred to as the PVA mask) with uniformly dispersed carbon is laminated onto the non-PET film side of the anisotropic light diffusion film composition layer No. 1 using a laminator. The resulting laminate is heated to 60°C, and while maintaining a constant temperature, parallel light emitted from an ultraviolet irradiation unit (manufactured by Hamamatsu Photonics Co., Ltd., trade name: L2859-01) is irradiated from the PVA mask surface at an intensity of 2.0 mW / cm². 2 Irradiate for 30 seconds. During this time, the angle of the irradiation light is such that it is not tilted from the normal direction of the anisotropic light diffusion film composition layer No.1.
[0347] The PVA mask and PET film are peeled off from the obtained laminate to obtain the anisotropic light diffusion film No.1 of Example 1, which is a single-layer anisotropic light diffusion layer No.1.
[0348] In addition, the thickness of the anisotropic light diffusion film No.1 is 40 μm, and the average height of the columnar structure is 40 μm.
[0349] [Example 2]
[0350] Except for changing component (A) to 10 parts by weight of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name: A-BPEF-2, refractive index: 1.62 (25°C), number of aromatic rings in the substituents of the fluorene skeleton: 2) and 90 parts by weight of m-phenoxybenzyl acrylate (refractive index: 1.57 (25°C), viscosity: 18 mPa·s (25°C)), the same method as in Example 1 was used to obtain the anisotropic light diffusion film No.2 of Example 2 as a monolayer anisotropic light diffusion layer No.2.
[0351] In addition, the thickness of the anisotropic light diffusion film No.2 is 40 μm, and the average height of the columnar structure is 40 μm.
[0352] [Example 3]
[0353] In the formulation of Example 2, except that component (C) was changed to 20 parts by weight of epoxy plasticizer (manufactured by DIC Company, trade name: Epicizer (registered trademark) W-100-EL, viscosity: 500 mPa·s (25°C)), the same method as in Example 2 was used to obtain the anisotropic light diffusion film No.3 of Example 3 as a single-layer anisotropic light diffusion layer No.3.
[0354] In addition, the thickness of the anisotropic light diffusion film No.3 is 40 μm, and the average height of the columnar structure is 40 μm.
[0355] [Example 4]
[0356] In the formulation of Example 2, except that component (C) was changed to 20 parts by weight of liquid rubber plasticizer (manufactured by Kuraray, trade name: LIR (registered trademark)-390, viscosity: 400 mPa·s (38°C)), the same method as in Example 2 was used to obtain the anisotropic light diffusion film No.4 of Example 4 as a single-layer anisotropic light diffusion layer No.4.
[0357] In addition, the thickness of the anisotropic light diffusion film No.4 is 40 μm, and the average height of the columnar structure is 40 μm.
[0358] [Example 5]
[0359] In the formulation of Example 2, except that component (C) was changed to 20 parts by weight of UV-curable liquid rubber plasticizer (manufactured by Kuraray, trade name: UC-203M, viscosity: 190 mPa·s (38°C)), the same method as in Example 2 was used to obtain the anisotropic light diffusion film No. 5 of Example 5 as a single-layer anisotropic light diffusion layer No. 5.
[0360] In addition, the thickness of the anisotropic light diffusion film No. 5 is 40 μm, and the average height of the columnar structure is 40 μm.
[0361] [Example 6]
[0362] For a laminate in which a PVA mask is stacked on an anisotropic light diffusion film composition layer, parallel light rays emitted from the incident irradiation unit are transformed into linear light rays by a directional diffusion element with an aspect ratio of 40. The angle at which the linear light rays are irradiated is in a direction orthogonal to both the direction of the light rays diffused by the directional diffusion element and the thickness direction of the anisotropic light diffusion film composition layer (hereinafter referred to as the MD direction), and the irradiation is carried out without tilting from the normal direction of the anisotropic light diffusion film composition layer. Otherwise, by performing the same method as in Example 2, the anisotropic light diffusion film No. 6 of Example 6, which is a single-layer anisotropic light diffusion layer No. 6, is obtained.
[0363] In addition, the thickness of the anisotropic light diffusion film No. 6 is 40 μm, and the average height of the columnar structure is 40 μm.
[0364] [Example 7]
[0365] For a stack in which a PVA mask is stacked on an anisotropic light diffusion film composition layer, parallel light rays emitted from the incident irradiation unit are converted into linear light rays by a directional diffusion element with an aspect ratio of 3. The linear light rays are irradiated at an angle in the MD direction from the normal direction of the anisotropic light diffusion film composition layer without tilting. Otherwise, the same method as in Example 2 is used to obtain the anisotropic light diffusion film No. 7 of Example 7, which is a single-layer anisotropic light diffusion layer No. 7.
[0366] In addition, the thickness of the anisotropic light diffusion film No.7 is 40 μm, and the average height of the columnar structure is 40 μm.
[0367] [Example 8]
[0368] Except that the thickness of the anisotropic light diffusion film No. 8 is 30 μm and the average height of the columnar structure is 30 μm, the anisotropic light diffusion film No. 8 of Example 8 was obtained by the same method as in Example 7, which is a single-layer anisotropic light diffusion layer No. 8.
[0369] [Comparative Example 1]
[0370] Except for not using materials that are (C) components, the anisotropic light diffusion film a of Comparative Example 1, which is a monolayer anisotropic light diffusion layer a, was obtained by the same method as in Example 1.
[0371] In addition, the thickness of the anisotropic light diffusion film a is 40 μm, and the average height of the columnar structure is 40 μm.
[0372] [Comparative Example 2]
[0373] Except for not using materials that are (C) components, the anisotropic light diffusion film b of Comparative Example 2, which is a monolayer anisotropic light diffusion layer b, was obtained by the same method as in Example 2.
[0374] In addition, the thickness of the anisotropic light diffusion film b is 40 μm, and the average height of the columnar structure is 40 μm.
[0375] [Comparative Example 3]
[0376] Except for changing component (C) to 20 parts by weight of styrene-isoprene-styrene (SIS) copolymer (manufactured by Kuraray, trade name: HYBRAR (registered trademark) 5127, glass transition temperature: 8°C), the same method as in Example 1 was used to obtain the anisotropic light diffusion film c of Comparative Example 3, which is a monolayer anisotropic light diffusion layer c.
[0377] In addition, the thickness of the anisotropic light diffusion film c is 40 μm, and the average height of the columnar structure is 40 μm.
[0378] (Evaluation Method)
[0379] The anisotropic light diffusion films of the embodiments and comparative examples of the present invention, prepared in the manner described above, were evaluated as follows.
[0380] [Thickness of the anisotropic light diffusion film]
[0381] A cross-section of the film was formed using a slicer and observed using an optical microscope. On this cross-section, the lengths connecting the film surface to its opposite side in a direction perpendicular to the film plane (thickness direction) were measured at 10 locations. The average of these measurements was taken as the thickness of the anisotropic light-diffusing layer.
[0382] [Average height of the anisotropic light diffusion layer columnar structure]
[0383] With one surface of the anisotropic light diffusion layer (anisotropic light diffusion film) as the bottom and the other surface as the top, the anisotropic light diffusion layer was placed horizontally. Using an optical microscope, the height of 20 columnar structures from the bottom to the top was measured, and their average value was taken as the average height of the columnar structures of the anisotropic light diffusion layer.
[0384] [Linear transmittance]
[0385] useFigure 7 The Goniophotometer (manufactured by GENESIA), which allows for arbitrary variation of the light projection angle of the light source and the light reception angle of the detector, was used to evaluate the linear transmittance of the anisotropic light diffusion film in the examples and comparative examples.
[0386] like Figure 7 As shown, samples 110 of the anisotropic light diffusion films of the embodiments and comparative examples are disposed between the light source 201 and the detector 202. Here, the light source 201 and the detector 202 are fixed. In this evaluation, the incident angle is set to 0° when the irradiation light I from the light source 201 is incident from the normal direction of the anisotropic light diffusion film, and the anisotropic light diffusion film is configured to be arbitrarily rotated about a direction orthogonal to the MD direction and the thickness direction of the anisotropic light diffusion film (hereinafter referred to as the TD direction) as the central axis L.
[0387] Next, the anisotropic light diffusion films of the configured embodiments and comparative examples were continuously rotated in 1° increments within a range of -75° to 75°, and the amount of light transmitted in the straight direction (linear transmitted light amount) at each incident light angle was measured. Furthermore, the linear transmitted light amount was measured by determining the wavelength in the visible light region using a visibility filter. Moreover, without passing through the anisotropic light diffusion film, the ratio of the linear transmitted light amount to the linear transmitted light amount (incident light amount, incident light amount) directly irradiated from the light source 201 to the detector 202 was obtained as the linear transmittance (%). In this invention, the linear transmittance at 0°, 15°, and 45° was obtained.
[0388] Aspect Ratio
[0389] The surfaces (ultraviolet-irradiated side during fabrication) of the anisotropic light diffusion layers (anisotropic light diffusion films) of the examples and comparative examples were observed using an optical microscope. The diameters (diameter or major and minor axes) of any 20 columnar structures were measured, and the average values were obtained. Based on the obtained diameters, the aspect ratio was determined. When the cross-sectional shape was elliptical and had both major and minor axes, the average major axis / average minor axis was set as the aspect ratio. When the cross-sectional shape was circular and only had the diameter, the aspect ratio was set to 1.
[0390] [Dynamic viscoelasticity]
[0391] Measurements were performed using a Hitachi High-Tech Dynamic Mechanical Spectrometer (trade name: DMS6100) according to JIS K 7244-1, in tensile mode, at a frequency of 1 Hz, a load of 10 mN, a measurement temperature range of -50 to 100 °C, and a heating rate of 3 °C / min. Based on the obtained storage modulus (E'), loss modulus (E''), and loss tangent (tanδ), values for -15 °C, 25 °C, and 60 °C were obtained. Furthermore, the lowest peak temperature on the low-temperature side of tanδ was also determined.
[0392] In addition, the evaluation criteria for dynamic viscoelasticity (storage modulus, loss modulus, and loss tangent) are as follows.
[0393] (Energy storage modulus)
[0394] A score of "○" (good) is given when all of the following conditions are met, and a score of "×" (bad) is given when none of the conditions are met.
[0395] -15℃: 1.0×10 7 Pa ~ 2.0 × 10 9 Pa
[0396] 25℃: 1.0×10 7 Pa ~ 2.0 × 10 9 Pa
[0397] 60℃: 1.0×10 6 Pa ~ 2.0 × 10 8 Pa
[0398] (Loss modulus)
[0399] A score of "○" (good) is given when all of the following conditions are met, and a score of "×" (bad) is given when none of the conditions are met.
[0400] -15℃: 1.0×10 7 Pa ~ 2.0 × 10 9 Pa
[0401] 25℃: 1.0×10 7 Pa ~ 2.0 × 10 9 Pa
[0402] 60℃: 1.0×10 6 Pa ~ 2.0 × 10 8 Pa
[0403] (Loss tangent)
[0404] The code is marked "○" (good) when the following conditions are met, and "×" (bad) when they are not met.
[0405] -15~60℃: 0.07~0.8
[0406] [Bending characteristics]
[0407] The anisotropic light diffusion films of the embodiments and comparative examples were held for at least 10 minutes at various temperature environments of -15°C, 25°C, and 60°C. Subsequently, at each temperature environment, one end of the anisotropic light diffusion film of the embodiments and comparative examples held at each temperature environment was moved along... A 2mm stainless steel cylindrical rod was bent 180° and returned to its original flat shape. The condition of the anisotropic light diffusion film of the embodiment and comparative example at this time was visually confirmed (whether there are cracks or wrinkles).
[0408] [Blinking]
[0409] 1. Fabrication of the anti-glare layer stack
[0410] The following ingredients were used as binder resins: 100 parts by weight of polyurethane acrylate (manufactured by DIC Corporation, trade name: UNIDIC (registered trademark) 17-806), 1.56 parts by weight of porous silica particles (manufactured by Fuji Silicon Chemical Co., Ltd., trade name: Sylophobic (registered trademark) 702, weight-average particle size: 2.5 μm, refractive index: 1.46), 1.35 parts by weight of porous silica particles (manufactured by Fuji Silicon Chemical Co., Ltd., trade name: Sylophobic (registered trademark) 100, weight-average particle size: 1.4 μm, refractive index: 1.46), and 3 parts by weight of photopolymerization initiator (IGM Resins). A composition for an anti-glare layer with a solid content of 32% by weight was prepared by mixing 0.2 parts by weight of a leveling agent (manufactured by DIC, trade name: PC4100, 10% solids) with a toluene / cyclopentanone (CPN) mixed solvent (70 / 30 by weight).
[0411] The above-mentioned anti-glare layer composition was coated onto a triacetyl cellulose membrane (manufactured by Konica Minolta Opto, trade name: KC8UX2M, thickness: 80 μm) as the light-transmitting substrate using a comma-shaped coating machine (registered trademark). After heating at 80°C for 1 minute, the membrane was irradiated with a high-pressure mercury lamp to accumulate a light intensity of 300 mJ / cm². 2 By exposing ultraviolet light, an anti-glare layer laminate with an anti-glare layer (thickness: 5μm) is obtained on a light-transmitting substrate.
[0412] Furthermore, the anti-glare layer of the fabricated anti-glare layer was measured using a haze meter (trade name: NDH-2000) manufactured by Nippon Denshoku Kogyo Co., Ltd., according to JIS K7136-1:2000. The results showed an internal haze of 1.5% and an external haze of 25%. In addition, the arithmetic mean roughness (Ra) was measured using a surface roughness measuring machine (trade name: Surfcorder SE500) manufactured by Kosaka Labs Co., Ltd., according to JIS B0601:2013, with a result of 0.35 μm.
[0413] 2. Fabrication of a transparent adhesive layer with PET film
[0414] 100 parts by weight of an acrylic adhesive (manufactured by Soken Chemical Co., Ltd., trade name: SK-Dyne (registered trademark) 1811L) and 0.45 parts by weight of a curing agent (manufactured by Soken Chemical Co., Ltd., trade name: L-45) were mixed in a solvent of 15 parts by weight of toluene and 4 parts by weight of ethyl acetate to obtain a coating solution. The coating solution was applied to a 100 μm thick PET film (manufactured by Toyobo Co., Ltd., trade name: A4360) using a coater. After obtaining the coating film, it was dried in a clean oven with the drying oven temperature set to 80°C, thereby obtaining a transparent adhesive layer with a thickness of 15 μm and a PET film.
[0415] In addition, the total light transmittance of the transparent adhesive layer with PET film was measured using a haze meter (trade name: NDH-2000) manufactured by Nippon Denshoku Kogyo Co., Ltd., according to JIS K7361-1:1997, and the result was 91%.
[0416] 3. Manufacturing of display film
[0417] One side of the anisotropic light diffusion film of each of the prepared embodiments and comparative examples is bonded to the light-transmitting substrate side of the prepared anti-glare layer laminate via a transparent adhesive layer with a PET film, thereby obtaining display films 1 to 8 of Examples 9 to 16 and display films a to c of Reference Examples 1 to 3. Furthermore, the prepared anti-glare layer laminate is directly used as anti-glare layer laminate No. 1 of Comparative Example 4. The relationship between these constituent components and the structure of the prepared display film or anti-glare layer laminate is shown in Table 5.
[0418] 4. Flashing evaluation
[0419] For the anisotropic light diffusion film side of the display films 1-8 of Examples 9-16 and the display films a-c of Reference Examples 1-3, or the light-transmitting substrate side of the anti-glare layer laminate No.1 of Comparative Example 4, after bonding the prepared transparent adhesive layer with a PET film to a commercially available organic EL panel, the presence or absence of flickering in the output image was visually confirmed.
[0420] The results for linear transmittance and aspect ratio are shown in Table 1, the results for dynamic viscoelasticity are shown in Tables 2 and 3, the results for bending properties are shown in Table 4, and the results for scintillation are shown in Table 5.
[0421] Table 1
[0422] Table 2
[0423] Table 3
[0424] Table 4
[0425] Table 5
[0426] Industrial applicability
[0427] According to the present invention, an anisotropic light diffusion film, a display film using the anisotropic light diffusion film, and a display using the display film can be provided. The anisotropic light diffusion film will not crack, wrinkle, or other abnormalities even when used in displays or windows that require bending, even at temperatures ranging from -15°C to 60°C.
[0428] Explanation of reference numerals in the attached figures
[0429] 1: Anti-glare layer; 1a: First side; 1b: Second side; 3: Anisotropic light diffusion film; 5: Transparent substrate; 7: Transparent adhesive layer; 9: Anti-glare layer laminate; 10, 11, 12: Display film; 30: Anisotropic light diffusion layer; 31: Matrix region; 32: Columnar region; 33: Columnar structure; 110: Sample; 201: Light source; 202: Detector; 300: Light source; 301, 302: Directional diffusion element; 303: Uncured resin composition layer.
Claims
1. An anisotropic light diffusion film having an anisotropic light diffusion layer, said anisotropic light diffusion layer being formed by photopolymerization of a composition comprising a photopolymerizable compound, a photopolymerization initiator, and at least one plasticizer selected from ester-based, epoxy-based, and liquid rubber-based materials, characterized in that... The anisotropic light diffusion layer has a matrix region and a columnar region, wherein the columnar region is composed of multiple columnar structures with a refractive index different from that of the matrix region.
2. The anisotropic light diffusion film according to claim 1, characterized in that, The energy storage modulus of the anisotropic light diffusion layer at -15°C is 1.0 × 10⁻⁶. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7 Pa ~ 2.0 × 10 9 Pa, The energy storage modulus of the anisotropic light diffusion layer at 25°C is 1.0 × 10⁻⁶. 7 Pa ~ 2.0 × 10 9 Pa and loss modulus are 1.0 × 10 7 Pa ~ 2.0 × 10 9 Pa, The energy storage modulus of the anisotropic light diffusion layer at 60°C is 1.0 × 10⁻⁶. 6 Pa ~ 2.0 × 10 8 Pa and loss modulus are 1.0 × 10 6 Pa ~ 2.0 × 10 8 Pa.
3. The anisotropic light diffusion film according to claim 2, characterized in that, The loss tangent of the anisotropic light diffusion layer is 0.07 to 0.8 at temperatures ranging from -15°C to 60°C.
4. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The peak temperature of the lowest temperature side of the loss tangent of the anisotropic light diffusion layer is below 0°C.
5. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The plasticizer is incorporated in a proportion of less than 30% of the total composition.
6. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The linear transmittance at an incident light angle of 0° is greater than 1% and less than 20%. The linear transmittance at an incident light angle of 15° is greater than 1% and less than 20%. The linear transmittance at an incident light angle of 45° is greater than 30% and less than 80%.
7. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The aspect ratio of the columnar structure at the section perpendicular to the column axis is less than 2.
8. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The aspect ratio of the columnar structure at the section perpendicular to the column axis is 2 to 40.
9. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The thickness of the anisotropic light diffusion layer is 10 μm to 60 μm.
10. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The plasticizer is a photocurable compound.
11. The anisotropic light diffusion film according to any one of claims 1 to 3, characterized in that, The plasticizer is a thermosetting compound. The composition also includes a curing agent. The anisotropic light diffusion layer is composed of light and thermally polymerized components added during the photopolymerization process.
12. A film for a display, characterized in that, The display film has an anisotropic light diffusion film as described in any one of claims 1 to 3 and an anti-glare layer on the visually verifiable side of the anisotropic light diffusion layer.
13. The display film according to claim 12, characterized in that, The arithmetic mean roughness of the anti-glare layer is 0.05 μm to 1.00 μm.
14. A display, characterized in that, The display has the display film of claim 12 in such a way that the anti-glare layer is the most visually verifiable side.
Citation Information
Patent Citations
Resin composition, coating for forming antiglare layer, antiglare film, and display using the same
JP2010248451A
Anti-glare layer forming coating, and Anti-glare film, and display device using the same
JP2010256882A
Antiglare film and display using the same
JP2011013238A
Anisotropic optical film
JP2015191178A
Light diffusion control film and method of manufacturing light diffusion control film
JP2019144418A
